2021
DOI: 10.1590/0037-8682-0576-2020
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of the larvicidal activity of extracts and fractions from Ocotea nutans (Nees) Mez against Aedes aegypti

Abstract: INTRODUCTION: Aedes aegypti is the main vector of dengue and yellow fever. Recently, the use of plant-sourced larvicides has gained momentum. METHODS: The hydroethanolic extracts and fractions of Ocotea nutans leaves and stems were bioassayed to determine the larvicidal efficacy of these samples. RESULTS: S-HEX (hexane fraction from the crude stem extract) demonstrated high potential for controlling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In further studies with the hexanic fraction of the crude extract of Ocotea nutans (Nees.) Mez stem conducted by Betim et al (2021), the results demonstrated a high potential to control L3 larvae, with LC of 50 14.14 µg/mL. Perewalo et al (2021) when evaluating the larvicidal activity of the alkaloid S-(+)-dicentrine extracted from galls of Ocotea puberula (Rich.)…”
Section: Discussionmentioning
confidence: 99%
“…In further studies with the hexanic fraction of the crude extract of Ocotea nutans (Nees.) Mez stem conducted by Betim et al (2021), the results demonstrated a high potential to control L3 larvae, with LC of 50 14.14 µg/mL. Perewalo et al (2021) when evaluating the larvicidal activity of the alkaloid S-(+)-dicentrine extracted from galls of Ocotea puberula (Rich.)…”
Section: Discussionmentioning
confidence: 99%